The nature of the community of the Dead Sea scrolls (with particular reference to the manual of discipline) and its relation to the church of the New Testament - Draper, Jonathan A (Rhodes University, Faculty of Divinity, Department of Divinity, 1977)
The scope of our examination of the ideas and beliefs of the Qumran sect and the Church of the New Testament is limited to what contributes to our understanding of the nature of the respective communities. No attempt is made to present a full theological examination of the concepts which arise. The aim is not an exhaustive treatment, but rather to suggest areas where the beliefs of the communities throw light on each other. Our method is to begin by establishing the beliefs of the Qumran sect in each case, with particular reference to the Manual of Discipline, and then comparing this with the corresponding concept in the New Testament. This avoids the danger of reading back later Christian ideas into our treatment of the Scrolls. In our examination of the New Testament texts, we shall not assume that they constitute a unity nor that they can be taken at face value, but that they bear the marks of the interests of the early Church and of the conflicting tendencies and practices which marked its development. Consequently the tools of Form, Source and Redaction Criticism are utilized where they can contribute to our purpose. Chapter 1, p. vi.
Keywords: Dead Sea scrolls; Dead Sea scrolls -- Criticism, interpretation, etc.; Apocalyptic literature -- History and criticism; Qumran community